2020
DOI: 10.1016/j.cmet.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Restricts Serine Metabolism to Preserve Regulatory T Cell Function

Abstract: Highlights d Ablation of Gclc in Tregs causes autoimmunity and increases anti-tumor responses d Gclc-derived GSH is needed for the suppressive function of Tregs in vitro and in vivo d GSH in Tregs regulates serine concentrations and metabolism. which impact mTOR and FoxP3 d Serine-and glycine-deficient diet rescues mutant mice from lethal inflammation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 82 publications
(115 reference statements)
4
121
0
1
Order By: Relevance
“…Accordingly, dietary intervention in the form of feeding the mutant mice on serine/glycine‐deficient chow prevents the onset of autoimmunity. In line with this finding, dampening of serine metabolism reinstated the suppressive function of Tregs, firmly linking serine metabolism to Treg function [61].…”
Section: Overview Of Metabolic Control In Treg Cellsmentioning
confidence: 75%
See 4 more Smart Citations
“…Accordingly, dietary intervention in the form of feeding the mutant mice on serine/glycine‐deficient chow prevents the onset of autoimmunity. In line with this finding, dampening of serine metabolism reinstated the suppressive function of Tregs, firmly linking serine metabolism to Treg function [61].…”
Section: Overview Of Metabolic Control In Treg Cellsmentioning
confidence: 75%
“…Lastly, it was shown that increased Glut1 expression in murine Tregs enhances glycolysis and proliferation driven by mTORC1. The increased mTORC1 activity impairs tTreg and pTreg suppressive capacity and decreases FoxP3 expression both in vitro and in vivo [22,61].…”
Section: Overview Of Metabolic Control In Treg Cellsmentioning
confidence: 99%
See 3 more Smart Citations